Regionalne ujednolicenie prawa prywatnego międzynarodowego w Skandynawii ze szczególnym uwzględnieniem spraw spadkowych - Klimala, Jagoda (Problemy Prawa Prywatnego Międzynarodowego, 2021)
The aim of the following article is to introduce characteristics of the Nordic countries’ cooperation in the field of private international law, with particular emphasis on legislative cooperation concerning matters of inheritance law. The study discusses the genesis, characteristics and methods of legislative cooperation, along with selected Nordic conventions on private international law. As an example of a legal act of such kind, the article presents the Convention of 19 November 1934 comprising private international law provisions on succession, wills and estate administration, the detailed analysis of which was based on the author’s translation of the act from Swedish to Polish. Selected detailed issues discussed in the content of the Convention were also presented, some of which were compared to the solutions adopted by Regulation (EU) No 650/2012 of the European Parliament and of the Council of 4 July 2012.